The Ins and Outs of Death in the Iron Age: Complex Funerary Treatments at Broxmouth Hillfort, East Lothian. Issue 1 (9th January 2013) - Armit, Ian; Neale, Naomi; Shapland, Fiona; Bosworth, Hannah; Hamilton, Derek; Mckenzie, Jo
Summary: Evidence for Iron Age funerary treatments remains sporadic across Britain and formal cemeteries are especially elusive. One important exception is Broxmouth hillfort, East Lothian, excavated during the late 1970s but not yet published. New analysis of the human remains from Broxmouth provides evidence for three distinct populations: a formal cemetery outside the hillfort, isolated graves within the ramparts, and a scatter of disarticulated fragments from a range of domestic and midden contexts. The latter group in particular provides significant evidence for violent trauma; isotopic evidence suggests that they may be the remains of outsiders. Together the human remains shed light on complex and changing attitudes to death and the human body in Iron Age Britain. The material from Broxmouth is considered in the light of emerging evidence for fluid and pluralistic treatments of the dead in the Iron Age of south‐east Scotland.